Specific function of vitamin D in bone - Dennisa Putri Ramadhani; Hammanda AD; Salsabila Azzahra; Akbar Rizkyadsyah; Anis Ulayya; Miftahul Huda Fendiyanto (FoundAE, 2024)
There are two sources of vitamin D, namely from food and sun exposure. The content of vitamin D is given beneficial in bone and mineral metabolism. Vitamin D helps absorption of calcium in the intestines, thereby accelerating bone mineralization. Bone metabolism is a complex process that occurs throughout life. Very high doses of vitamin D can stimulate an increased rate of bone loss. Vitamin D deficiency causes bone demineralization. Which can cause a decrease in calcium absorption. The functions of these metabolites vary widely in vital metabolic pathways. This review aims to determine the specific function of vitamin D in bone. The search for the data base was carried out by the analytical method. Vitamin D which is absorbed from food or comes from the skin turns into an active form in the form of 1,25- (OH) 2-D3 which will enter the bloodstream, playing an important role in bone and extra-skeletal health.